2011
DOI: 10.1080/00268976.2010.530302
|View full text |Cite
|
Sign up to set email alerts
|

Application of the singlet reference interaction site model to the primitive model double layer

Abstract: 2011) Application of the singlet reference interaction site model to the primitive model double layer,The Singlet Reference Interaction Site Model (SRISM) is employed to a structural study of the planar electric double layer using the primitive model of the double layer in which the solvent is implicit, being characterized by a dielectric constant, the ions are represented by charged hard spheres, while the electrode is a uniformly charged flat surface. The primitive model double layer has the advantage that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…We reviewed the SRISM theory in detail in our previous paper [1] and there is little need to repeat this discussion. Two closures were examined, the hypernetted chain (HNC) and Kovalenko-Hirata (KH) closures.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed the SRISM theory in detail in our previous paper [1] and there is little need to repeat this discussion. Two closures were examined, the hypernetted chain (HNC) and Kovalenko-Hirata (KH) closures.…”
Section: Theorymentioning
confidence: 99%
“…In a recent paper [1], two of us together with Bhuiyan (WBH) applied the Singlet Reference Interaction Site Model (SRISM), using both the hypernetted chain (HNC) and Kovalenko-Hirata (KH) closures, to the study of density profiles of the double layer formed by a restricted primitive model (RPM) at low electrolyte densities and concluded that the HNC closure was preferable. However, that study was an introductory one whose purpose was to apply and test our programs to the previously studied systems.…”
Section: Introductionmentioning
confidence: 99%